Model Regresi Kuadratik pada Pengepresan Biji Kemiri - Dita Anies Munawwaroh; Abdul Syukur Alfauzi; Adhy Purnomo Purnomo; Ali Sai’in Sai’in; Elfrida Rizky Riadini (Journal of Mechanical Engineering and Applied Technology, 2026)
Vegetable oil (seeds oil) is produced from seeds. To obtain vegetable oil, a seed extraction machine is required. Seed pressing machines have specifications based on their extraction method. In this study, candlenut seed oil was produced using an extraction machine using the extrusion method. This process uses a combination of heating, friction, and high pressure. A quadratic regression model was used to predict the effect of temperature on the volume of oil produced. The results showed that the optimal temperature for producing candlenut oil is 95.96 degrees Celsius.